2013
DOI: 10.1080/10826076.2012.706858
|View full text |Cite
|
Sign up to set email alerts
|

An Assay of Total Glutathione and Glutathione Disulfide in Human Whole Blood and Plasma Using a High-Performance Liquid Chromatography With Fluorescence Detection

Abstract: & A method is described here for the determination of total glutathione and glutathione disulfide in human whole blood and plasma with a suitable sample preparation procedure to prevent glutathione oxidation and glutathione disulfide hydrolysis. Whole blood samples were obtained from a group of blood donors. After adequate sample preparation, the samples were derivatized with ortho-phthaldialdehyde to form a stable, highly fluorescent tricyclic derivative. Reverse-phase column chromatography was used for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…GSSG is only stable when using metaphosphoric acid with NEM, but for a maximum of 1 h; the use of other acids, particularly PCA, causes rapid decrease of GSSG. It is reported that GSH–NEM is unstable and excess of NEM may result in loss of GSSG (Kanďár et al ., ). On the other hand, it is stated that NEM blocks the glutathione reductase (GR, EC 1.8.1.7), thereby preventing backward GSSG reduction to GSH (Floreani et al ., ).…”
Section: Determination Of Oxidized and Reduced Forms Of Selected Antimentioning
confidence: 97%
See 3 more Smart Citations
“…GSSG is only stable when using metaphosphoric acid with NEM, but for a maximum of 1 h; the use of other acids, particularly PCA, causes rapid decrease of GSSG. It is reported that GSH–NEM is unstable and excess of NEM may result in loss of GSSG (Kanďár et al ., ). On the other hand, it is stated that NEM blocks the glutathione reductase (GR, EC 1.8.1.7), thereby preventing backward GSSG reduction to GSH (Floreani et al ., ).…”
Section: Determination Of Oxidized and Reduced Forms Of Selected Antimentioning
confidence: 97%
“…It is also possible that, at room temperature, the enzyme activity of GGT is sufficient to catalyse peptide bond hydrolysis between glutamate and cysteine. That could explain the sharp decline of TGSH during 1 h at room temperature and the only slight decline at 4°C (Kanďár et al ., ). Appropriate derivatization with a suitable reagent is needed to increase sensitivity, and also the selectivity.…”
Section: Determination Of Oxidized and Reduced Forms Of Selected Antimentioning
confidence: 97%
See 2 more Smart Citations
“…Under the optimu conditions, a "cumulative" regression equation was obtained by assimilating the resu from 40 standard solutions analyzed in different working days (n = 8), setting t calibration curve more representative by embracing any potential variations. Additionally, the within-day precision was calculated at two GSH concentrati values, 100 and 350 µmol L −1 , by repetitious measurements of different paper devices ( 5). The intra-day relative standard deviation (RSD) was 6.2% and 3.1%, respectively, these two concentration values, while the inter-day RSD was 7.3% and 4.4%, respective For both intra-day and inter-day precision experiments, de-ionized water was utilized the solvent for standard solutions.…”
Section: Figures Of Meritmentioning
confidence: 99%